Public Perceptions About Use of Siak River Fishermen In Tanjung Rhu District Fifty Pekanbaru Riau Province - Veny Fitriyani; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on March 10th until March 20th, 2013. This study aims to determine the public perception about the use of the Siak River fishermen. The method used in this study is a survey method and determination of the respondents in this study is